2005
DOI: 10.1161/01.str.0000173406.04891.8c
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hypoxia/Ischemia Is Associated With Decreased Inflammatory Mediators After Erythropoietin Administration

Abstract: Background and Purpose-Erythropoietin (EPO), a hematopoietic growth factor, has been shown to be neuroprotective when administered as either a pretreatment or posttreatment. This study tested the hypothesis that one of the mechanisms of protection afforded by posttreatment with recombinant human EPO (rh-EPO) is an anti-inflammatory effect via inhibition of interleukin (IL)-1␤. Methods-Seven-day-old rat pups were subjected to unilateral carotid artery ligation followed by 90 minutes of hypoxia (8% O 2 at 37°C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
119
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(126 citation statements)
references
References 25 publications
(41 reference statements)
6
119
0
1
Order By: Relevance
“…The apoptotic cells after 48 h of HI insult can be involved in other factors, such as inflammatory cytokines, in relation to microglial activation. IL-1beta (IL-1␤) expression gradually increases during 1-14 d after HI insult, and erythropoietin inhibits microglial activation and reduces brain damage (33). On the contrary, under the condition of hypoglycemia and hypoxemia by HI insult, IL-1␤ directly or indirectly attacks neurons and leads to neuronal cell death (34).…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic cells after 48 h of HI insult can be involved in other factors, such as inflammatory cytokines, in relation to microglial activation. IL-1beta (IL-1␤) expression gradually increases during 1-14 d after HI insult, and erythropoietin inhibits microglial activation and reduces brain damage (33). On the contrary, under the condition of hypoglycemia and hypoxemia by HI insult, IL-1␤ directly or indirectly attacks neurons and leads to neuronal cell death (34).…”
Section: Discussionmentioning
confidence: 99%
“…8 NF-jB ''decoy'' (a new anti-gene approach) alleviates the hyperalgesia induced by spinal nerve ligation injury. 9 Furthermore, inhibition of IjB kinase (which phosphorylates IjB to activate NF-jB) reduces hyperalgesia in inflammatory and neuropathic pain models of rats. 22 Anti-inflammatory cytokine, IL-10, may inhibit a positive feed-forward loop between pro-inflammatory cytokines and NF-jB in both inflammation and neuropathic pain states.…”
Section: Discussionmentioning
confidence: 99%
“…6 rhEPO has neuroprotective effects in experimental models of central nervous system injury. [9][10][11] The possible mechanisms include anti-inflammation effects, 9-11 alterations in NF-jB activity, 21 and activation of glial cells 9 and antiapoptotic genes. 10,12 Few reports have suggested that systemically administered rhEPO can facilitate the recovery from behavioural changes during neuropathic pain associated with CCI, L5 spinal nerve crush, or nerve root injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of these cytokines in inflammation, edema formation, fibrosis and tissue remodeling has been well-documented. 24,25 For many years, EPO was considered to be a renally-produced, monolineage-specific hormone which functioned to stimulate the survival, proliferation and differentiation of erythroid cells. 6 However, several recent studies from our laboratory and others have shown that EPO has pleiotropic properties.…”
Section: Discussionmentioning
confidence: 99%